Pendampingan Pengelolaan Kritik dan Saran untuk Optimalisasi Kinerja FEBI Mart di IAIN Kediri - Rahmah, Zakiyah Zulfa; Sofiastuti, Nurriza; Santoso, Moh. Fathoni; Saka, Dijan Novia (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
FEBI Mart is a student-run canteen at the State Islamic Institute (IAIN) Kediri. As one of the campus facilities FEBI Mart plays an important role in providing consumption needs for students and the academic community, as well as being a model of participation-based business management. However, FEBI Mart faces various challenges, including the management of feedback that can affect the quality of service and the development of the canteen's performance. Criticism and suggestions that are not managed properly can become obstacles in FEBI Mart's optimization and growth efforts. This research aims to provide assistance in managing feedback to evaluate FEBI Mart’s performance. The assistance steps include identifying feedback collection mechanisms, analyzing the problems faced, and implementing an effective criticism and suggestion management system. The results of this assistance are expected to provide applicable recommendations to improve service quality, operational efficiency, and encourage FEBI Mart's growth to be better and develop sustainably. With optimal management, FEBI Mart is expected to be an example of a student business that is innovative and responsive to consumer needs.